تحديد بعض الأنماط الوراثية لفيروس التهاب القصبات المعدي المنتشرة في مزارع دجاج اللحم في سورية باستخدامRT-PCR - عبد العزيز, فهيم; سلهب, محمد; العمر, أنور; الجلاد, تمارة (Latakia University Journal -Biological Sciences Series, 2019)
Infectious bronchitis (IB) is a highly contagious disease, that affects chickens of all ages, and its risk and losses resulting from infection is greater in young birds. The disease is common throughout the world where chickens are produced commercially, and it appears in the field as a respiratory condition associated with a decrease in egg production , delayed growth and changes in the characteristics of laying hens. Pathological anatomy shows lesions in the bronchi, kidneys and egg production organs. This disease has several forms: respiratory, renal and reproductive form. It causes respiratory dysfunction , renal damage and decrease in egg production. The Infectious Bronchitis Virus (IBV) belongs to the family Coronaviridae. It has an envelope of S and M glycoproteins. IBV is an enveloped virus with a single-stranded, positive-sense RNA genome. Reverse transcription PCR technology is an effective technique for IBV detection, and compared to traditional detection methods PCR-based techniques are both sensitive and fast. This research was conducted to identify the infectious bronchitis virus with group specific primers of avian Coronaviruses in Coastal Area of Syria. 50 histological samples from broiler flocks were collected from eleven commercial broiler flocks and these samples were used for RNA extraction. General primers included XCE2+ and XCE2- that amplify all IBV serotypes were used. Primers MCE1+, BCE1+ and DCE1+ was used for amplifying the specific nucleotide sequence of Massachusetts, 4/91 and D274 serotypes, respectively. The results of this study showed that 80% of the sampled flocks were positive to IBV by RT-PCR. Moreover, the Massachusetts was the identified serotype of infectious bronchitis virus. The results provide the first molecular evidence for the presence of infectious bronchitis virus and Massachusetts, 4/91, D274 serotypes in Syria. التهاب القصبات الهوائية المعدي (IB) Infectious Bronchitis من الأمراض المعدية الوبائية التي تصيب الدواجن بكافة الأعمار، وتكون خطورتها والخسائر الناتجة أـكبر عند الطيور الفتية. ينتشر المرض في جميع أنحاء العالم حيث تتركز صناعة وإنتاج الدواجن المكثفة. يظهر المرض حقليا كحالة تنفسية تترافق بانخفاض إنتاج البيض وتغير مواصفاته عند الدجاج البياض، وتبيّن الصفة التشريحية المرضية آفات في القصبات والشعب الهوائية وفي الكليتين وفي أعضاء إنتاج البيض. ينتمي الفيروس المسبب Infectious Bronchitis Virus (IBV) إلى فصيلة الفيروسات التاجية Family Coronaviridae. وهي ذات غلاف مكون من بروتينات سكرية بنيوية S و M خاصة بالحمة. جينوم RNA وحيد السلسلة الإيجابية، والقفيصة ذات تناظر حلزوني. تقنية الـPCR التي تعتمد على النسخ العكسي للـRNA تقنية فعالة لكشف IBV بالمقارنة مع طرق الكشف التقليدية و تعرف التقنيات المستندة على الـPCR بأنها حساسة و سريعة. تم إجراء البحث لكشف وتحديد أنماط فيروس التهاب القصبات الهوائية المعدي باستخدام مجموعة من البادئات النوعية المتخصصة بالفيروسات التاجية الطيرية، ولهذا الهدف جُمعت 50 عينة مرضية من الأعضاء التي أظهرت آفات واضحة من مزارع دجاج اللحم المشتبه بإصابتها بالمرض في مناطق مختلفة من سورية. لاستخلاص الحمض النووي RNA من هذه العينات، استخدمت بادئات عامة تتضمن XCE2- و XCE2+ التي تكاثر أو تنسخ كل الأنماط المصلية للـIBV . واستخدمت البادئات التالية: +MCE1 ، BCE1+ و DCE1+ للتسلسل النكليوتيدي الخاص بالأنماط المصلية: ماساتشوسيتس ، 4/91, و D274 على الترتيب. أظهرت نتائج هذه الدراسة أن 80% من العينات إيجابية للـIBV باستخدام تقنية RT_PCR . وبيّنت أيضاً أن النمط المصلي الماساتشوسيتس هو النمط الشائع لفيروس التهاب القصبات الهوائية المعدي في سورية، وتقدم النتائج دليلاً جزيئياً لوجود الفيروس بالأنماط الثلاث ماساتشوسيتس ، 4/91 و D274.